Loan Management Effectiveness and Compliance in the Jakarta Provincial Government - Hamdani; Yonnedi, Efa (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — Empirical studies on regional loan management remain limited, particularly in contexts where local governments operate without central fiscal transfers. Jakarta’s unique case of maintaining budget surpluses while utilizing loans provides novel insights that contribute to the limited literature on loan management in developing countries. Research objectives — This research examines the effectiveness of loan utilization in Jakarta, which is unique among regional governments for operating without general allocation fund (DAU) transfers until 2023 and for consistently maintaining a budget surplus despite taking loans. Research Methods — A desk-based qualitative analysis was conducted using audited financial statements (LKPD) from 2015 to 2022, along with the unaudited 2023 budget realization report (LRA). Seven performance indicators were applied to rigorously assess the effectiveness of loan utilization. Empirical Result — The findings indicate inadequate loan performance. Jakarta only required loans in 2019, while the 2018 deficit could still be covered by net financing without borrowing. Moreover, of the six budget-year loans, three failed to comply with the provisions of Government Regulation Number 56 of 2018. Implications — The study recommends a rigorous examination of regional cash availability, based on the remaining budget calculation (SiLPA) or year-end cash balance, prior to loan issuance. The findings also highlight the importance of prognosis analysis of local cash in loan decisions, providing a theoretical contribution to public financial management and informing potential policy reforms in loan evaluation by the Ministry of Home Affairs and the Ministry of Finance.